A Study on the Economic and Social Impact of Colonial Railway Expansion: Evidence from British India (International Journal of Food and Nutritional Sciences, 2022)
This research examines the complex, varying outcomes of colonial rail development in late 19th and early 20th-century British India. We employ a mixed-methods approach that combines quantitative study of historical economic data with qualitative examination of social developments to examine how the introduction and growth of railroads transformed India’s economic landscape and social fabric. Our research shows that railroads had a very important positive influence on early industrialisation, agricultural commercialisation, and market integration, but these gains were not even distributed. The social influence was of equal significance as it worked to promote urbanisation, unhinge established ideas of social order, and put in place nationalistic and educational concepts. Yet, railroads also fostered certain colonial power structures and inequities. This thesis contributes to knowledge of the complex legacies of colonial infrastructure endeavours and their ongoing implications for socio-economic transformation in postcolonial contexts.